Methods to Evaluate Peanut Maturity for Optimal Seed Quality and Yield - Ethan T. Carter; Patrick Troy; Diane Rowland; Barry Tillman; Keith Wynne; Krystel Pierre; Michael Mulvaney (EDIS, 2016)
Determining when to dig is one of the most important economic decisions a grower must make. Peanut (Arachis hypogaea L.) poses a unique challenge for maturity determination because it is an indeterminate crop that forms pods underground. This 8-page fact sheet discusses maturity assessment methods as well as steps for collecting and evaluating a maturity sample. Written by Ethan Carter, Patrick Troy, Diane Rowland, Barry Tillman, Keith Wynn, Krystel Pierre, and Michael Mulvaney, and published by the UF Agronomy Department, September 2016.